Enterprise Architecture Model for Vocational High School - Wawa Wikusna (IJAIT (International Journal of Applied Information Technology), 2018)
Vocational High School (SMK) is established to prepare productive and competitive labor. Each SMK has the vision to be the best school that provides the best service to the stakeholders in generating the smart and competitive Indonesian people. The achievement of the mission would be succeeded by building an integrated information system at school. Currently, many SMKs do not have an information system development plan that suits the core business aspect as the primary drivers, such as the organizational issues, human resources, environment, information technology, and application development aspects. Therefore, the design of enterprise architecture model is needed to generate data architecture, application architecture, technology architecture, and direction of the implementation plan for the school. In this study, the authors designed the enterprise architecture for SMK that can build the achievement of school goals. The method used is Enterprise Architecture Planning (EAP). With the design of enterprise architecture, the development of information systems in SMK would have an appropriate and effective direction for achieving the goals.